2021
DOI: 10.1111/cts.13088
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacometabolomics identifies candidate predictor metabolites of an L‐carnitine treatment mortality benefit in septic shock

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…We excluded patients who were allocated to receive intravenous L-carnitine to focus on the metabolic trajectory of the disease course without any interference that may be introduced by the study drug. Furthermore, we have previously identified phenotypes of L-carnitine response ( 19 ). The trial protocol was approved by the institutional review board (IRB) of all 16 centers and registered with clinicaltrials.gov (NCT01665092) prior to patient enrollment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded patients who were allocated to receive intravenous L-carnitine to focus on the metabolic trajectory of the disease course without any interference that may be introduced by the study drug. Furthermore, we have previously identified phenotypes of L-carnitine response ( 19 ). The trial protocol was approved by the institutional review board (IRB) of all 16 centers and registered with clinicaltrials.gov (NCT01665092) prior to patient enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Serum was obtained from whole blood, frozen at –80°C, and shipped on dry ice to the University of Michigan College of Pharmacy Nuclear Magnetic Resonance (NMR) Metabolomics Laboratory to await metabolomics assays. Further details regarding sample processing from this trial have been reported elsewhere ( 19 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed descriptions of the blood sampling, handling, and processing from this cohort have been previously reported [26,30]. Briefly, baseline whole blood samples were collected at the time of clinical trial enrollment.…”
Section: Blood Sampling and Metabolomicsmentioning
confidence: 99%
“…Metabolomics, as an applied science, identifies small molecules in a biological sample [20]. In doing so, metabolomics provides a physiological "snapshot" and molecular phenotype of the host and has proven useful in differentiating patient outcomes and response to drug therapy in patients with sepsis [21][22][23][24][25][26][27]. As such, we sought to determine among mechanically ventilated patients with septic shock, if the baseline patient metabolic status could help distinguish CCI from patients with rapid recovery.…”
Section: Introductionmentioning
confidence: 99%